2014
DOI: 10.4238/2014.september.12.10
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative assessment of the effects of the EPHX1 Tyr113His polymorphism on lung and breast cancer

Abstract: ABSTRACT. The association between the microsomal epoxide hydrolase 1 gene (EPHX1) Tyr113His polymorphism and lung cancer and breast cancer risk has been reported in many recent studies, but there is no consensus among the results. Thus, we examined the association between the EPHX1 Tyr113His polymorphism and lung cancer through a meta-analysis. A comprehensive literature search was performed using the Pubmed and Embase databases. Odds ratios with 95% confidence intervals were used to assess the strength of ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 32 publications
(47 reference statements)
0
4
0
Order By: Relevance
“…Although the direct mechanisms linking EPHX1 and vitamin D are unclear, an in-vivo study showed that 1,25(OH) 2 D 3 increased the expression of EPHX1 and other phase I and phase II biotransformation enzymes in the intestinal tissue of vitamin D-deficient rats [ 54 ]. There is no known association between EPHX1 and breast cancer risk [ 55 ]. We do note that our results should be interpreted with caution as the EPHX1 CpG site that was strongly associated with 25(OH)D in our sample had a low ICC (< 0.5), meaning that the within-subject variability was larger than the between-subject variability.…”
Section: Discussionmentioning
confidence: 99%
“…Although the direct mechanisms linking EPHX1 and vitamin D are unclear, an in-vivo study showed that 1,25(OH) 2 D 3 increased the expression of EPHX1 and other phase I and phase II biotransformation enzymes in the intestinal tissue of vitamin D-deficient rats [ 54 ]. There is no known association between EPHX1 and breast cancer risk [ 55 ]. We do note that our results should be interpreted with caution as the EPHX1 CpG site that was strongly associated with 25(OH)D in our sample had a low ICC (< 0.5), meaning that the within-subject variability was larger than the between-subject variability.…”
Section: Discussionmentioning
confidence: 99%
“…A recent meta-analysis on rs1051740 SNP has suggested an association of the His allele with increased lung carcinoma risk in Asian, but not Caucasian populations (Wang et al 2013). Another meta-analysis confirmed that this SNP may be a risk factor for lung carcinoma in Asians, but observed its protective effect in Caucasians as well (Tan et al 2014). Two haplotypes constructed using eight EPHX1 SNPs were significantly associated with lung carcinoma risk in a population-based case-control study involving more than 4000 participants (Rotunno 2009).…”
Section: Ephx1 Role In Human Diseasementioning
confidence: 94%
“…These studies suggested that the presence of EPHX1 SNPs may significantly affect the risk of lung, upper aerodigestive tract, breast, bladder, and ovarian carcinomas (Jourenkova-Mironova et al 2000, Sarmanova et al 2004, Spurdle et al 2007, Khedaier et al 2008, Andrew et al 2009, Goode et al 2011, Tan et al 2014, Perez-Morales 2014). Two non-synonymous EPHX1 SNPs (rs72549341 and rs148240980) were recently predicted by in silico models as breast cancer susceptibility modifiers (Masoodi et al 2012) providing and intriguing hypothesis for further study.…”
Section: Ephx1 Role In Human Diseasementioning
confidence: 99%
“… 11 The 113His allele was shown to be a risk factor for lung carcinoma in Asians, whereas it was observed to have a protective effect in Caucasians in a recent meta-analysis. 46 Moreover, a protective role has been attributed to low mEH activity against childhood lymphoblastic leukemia. 47 Furthermore, a meta-analysis demonstrated a trend towards a protective effect of His139Arg SNP against colorectal cancer risk.…”
Section: Discussionmentioning
confidence: 99%